WHISTLEBLOWING SYSTEMS AS AN EFFORT TO PREVENT FRAUD IN STATE UNIVERSITIES WITH LEGAL RIGHTS (PTN-BH) - Rozali, Rozmita; Fitriani, Indah (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
The Integrity Zone was created to eliminate fraud, and one of the channels to prevent fraud was the whistleblowing system. This research aims at obtaining an overview of the implementation of the Whistleblowing System at Legal Entity State Universities (PTNBH) and the impact of its implementation on preventing fraud. The urgency of this research was to find out how much influence the whistleblowing system had as a mechanism for preventing fraud. This research methodology used a qualitative approach using in-depth interviews, the human resources used were the leaders of SPI ITB, IPB, and UGM, and then the data was analyzed using source triangulation and data triangulation. The results of this research found that with strong internal controls at the three PTNBHs, the whistleblowing system was not the main mechanism for preventing fraud. However, a whistleblowing system was still needed as public/stakeholder control to create good university governance.